PENGARUH PROFESIONALISME DAN PENGETAHUAN AUDITOR DALAM MENDETEKSI KEKELIRUAN TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS PADA KANTOR AKUNTAN PUBLIK DI KOTA MAKASSAR - Sufiati Sufiati; Muhammad Fadly Putra Utama (Contemporary Journal on Business and Accounting, 2021)
Purpose – Examine the effect of Auditor Professionalism and Auditor Knowledge to Detect Errors on Materiality Level Considerations in Public Accounting Firms in Makassar City. Design/methodology/approach – Multiple regression techniques. Findings – Auditor professionalism has a positive and significant effect on the Consideration of Materiality Levels. The Auditor's Knowledge to Detect Errors does not have a significant effect on the Consideration of Materiality Levels. Originality – Primary data obtained from of 34 auditors Public Accounting Firms in Makassar City. Keywords: Auditor Professionalism, Auditor Knowledge to Detect Errors, Consideration of Materiality Level Paper Type Research Result